A guide to between‐community functional dissimilarity measures - Lengyel, Attila; Botta‐Dukát, Zoltán (Ecography (Copenhagen), 2023)
One of the effective tools to study the variation between communities is the use of pairwise dissimilarity indices. Besides species as variables, the involvement of trait information provides valuable insight into the functioning of ecosystems. In recent years, a variety of indices have been proposed to quantify functional dissimilarity between communities. These indices follow different approaches to account for between‐species similarities in calculating community dissimilarity, yet they all have been proposed as straightforward tools. In this paper, we review the trait‐based dissimilarity indices available in the literature and identify the most important conceptual and technical properties that differentiate among them, and that must be considered before their application. We identify two primary aspects that need to be considered before choosing a functional dissimilarity index. The first one is the way communities are represented in the trait space. The three main types of representations are the typical values, the discrete sets using the combination of species × sites and species × traits matrices, and the hypervolumes. The second decision is the concept of dissimilarity to follow, including two options: distances and disagreements. We use the above scheme to discuss the available functional dissimilarity indices and evaluate their relations to each other, their capabilities, and accessibility.